DIVERSITY INDICES OF PLANKTON IN POWAI LAKE, MUMBAI, INDIA - Usman, Abubakar (Nigerian Journal of Fisheries, 2019)
Plankton species of Powai lake were investigated in five stations, designated as station A, B, C, D and E respectively. Sampling was done in the morning before 8:00am, on monthly basis for a period of twelve months (November 2016 to October 2017) covering pre-monsoon, monsoon and post-monsoon seasons and analysed. Pour-through method was adopted. The monthly trend of Shannon-Weiner index for the lake could be depicted as month of March >August >July= September= October>June> April>May> November> January> December> February. The species richness index ranged from 0.632 (October) to 1.095 (January). The minimum number (15001) of plankton species was recorded in station B whereas the maximum number (26320) was observed for station C. The concentration of dominance was highest in station A > D > C> B = E. Powai lake is fairly rich in terms of plankton abundance and diversity. More intensive studies of the plankton species in Indian lakes will lead to the documentations of other species and wider distribution of many others than those that were recorded in the current study. This will lead to greater understanding of the factor that controls the distribution of these species.